2011
DOI: 10.3390/cancers3011405
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer-Initiating Cells: Insights into Novel Treatment Strategies

Abstract: There is accumulating evidence that breast cancer may arise from mutated mammary stem/progenitor cells which have been termed breast cancer-initiating cells (BCIC). BCIC identified in clinical specimens based on membrane phenotype (CD44+/CD24−/low and/or CD133+ expression) or enzymatic activity of aldehyde dehydrogenase 1 (ALDH1+), have been demonstrated to have stem/progenitor cell properties, and are tumorigenic when injected in immunocompromized mice at very low concentrations. BCIC have also been isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…It is worth noting that the pathways identified by the three differentially upregulated miRNAs were very similar and related to both breast cancer and more general cancer development (e.g. ErbB, mTOR, TGFb and Wnt pathways) (31)(32)(33)(34)(35). We then also observed that the three miRNAs targeted pathways also related to insulin and other endocrine/metabolic pathways recognized in the ORDET cohort, as well as in other studies as pathways involved in breast cancer development (10,32,36).…”
Section: Leucocyte Mirnas Differentially Expressed In Ordet Samplessupporting
confidence: 70%
“…It is worth noting that the pathways identified by the three differentially upregulated miRNAs were very similar and related to both breast cancer and more general cancer development (e.g. ErbB, mTOR, TGFb and Wnt pathways) (31)(32)(33)(34)(35). We then also observed that the three miRNAs targeted pathways also related to insulin and other endocrine/metabolic pathways recognized in the ORDET cohort, as well as in other studies as pathways involved in breast cancer development (10,32,36).…”
Section: Leucocyte Mirnas Differentially Expressed In Ordet Samplessupporting
confidence: 70%
“…Fluorescence-activated cell sorting analysis (FACS) and/or magnetic-activated cell sorting analysis (MACS) are designed to isolate CSCs expressing specific biomarkers, such as CD44 + , CD24 − , EpCAM + , and ALDH hi , etc. [ 45 , 46 ]. The second strategy is to utilize biofunctions of CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 1–2% are breast cancer stem cells (BCSCs) and are believed to initiate and promote tumorigenesis . There is increasing evidence that these small fractions of BCSCs are responsible for metastasis, tumor recurrence, and resistance to chemotherapeutic agents . Previously, we and others reported that chemotherapeutic agents such as docetaxel, doxorubicin, or 5‐flurouracil (5‐FU) fail to inhibit the growth of BCSCs or to preferentially target and kill differentiated breast cancer cells .…”
Section: Introductionmentioning
confidence: 99%